EEG power spectral analysis and saccadic eye movement for true and false information - Elvina Febriyani Chandrawijaya; Ananta Yudiarso; Yusti Probowati Rahayu (University of Muhammadiyah Malang, 2022)
The purpose of this study was to examine the differences between the electroencephalography (EEG) power spectral analysis and saccadic eye movements (SEM)’s the response toward true and false information. The research method was conducted using an experimental design with true and false autobiographical information as stimuli. There were23 female participants aged between 19-24 years old (M=21,45; SD=1,5). The results showed a significant difference in the number of SEM between false information and true information. The EEG power is greater in the frontal, temporal and central areas for false information. Interestingly, we found a correlation between EEG power and SEM in detecting true and false information. Our result findings indicated evidence of multimodality by combining electroencephalography (EEG) and saccadic eye movement (SEM) to dissociate false and true information responses. The distinct dissociative process between true and false information can be used for memory studies and developing lie detectors.